Stable PbS quantum dot ink for efficient solar cells by solution-phase ligand engineering. Issue 26 (18th June 2019) - Gu, Mengfan; Wang, Yongjie; Yang, Fan; Lu, Kunyuan; Xue, Ye; Wu, Tian; Fang, Honghua; Zhou, Sijie; Zhang, Yannan; Ling, Xufeng; Xu, Yalong; Li, Fangchao; et al.
Abstract : A multiple-passivation strategy by solution-phase ligand engineering in lead halide exchanged QDs ink is presented, which result in remarkably improved colloidal stability of QDs ink and enhanced device performance. Abstract : Surface passivation is essential to realize high photovoltaic performance for solar cells based on PbS quantum dots (QDs). The recently developed solution-phase ligand-exchange strategy can greatly simplify the device fabrication process compared with the traditional layer by layer method. However, the surface hydroxyl ligand (OH) on the PbS QD surface, a main source of trap states, cannot be avoided in the solution-phase ligand-exchange process and has not been paid attention yet. Meanwhile, the unsatisfactory colloidal stability of current PbS QD ink is also a barrier for its industrial application and waiting for solutions. Here, we demonstrate a multiple-passivation strategy by solution-phase ligand engineering in lead halide exchanged QD ink. It was found that our facile approach can efficiently reduce the trap states of PbS QD ink by suppressing the amount of surface hydroxyl groups. Moreover, ligand engineering can also increase the interaction between QDs and solvent, which endows the QD ink with remarkably improved colloidal stability. As a result, a significant improvement of PCE from 9.99% to 11.18% and device stability were realized. Our results present a new passivation method for solution-phase ligand exchanged QD ink and the improved colloidal stability may help to boost the industrial application of PbS QD based solar cells.